Nurcholish Madjid’s Perspective on Interfaith Marriage: An Analytical Study - Izza Nabila; Yunita Wuladari (Universitas Sultan Ageng Tirtayasa, 2026)
This study explores Nurcholish Madjid’s perspective on interfaith marriage and its implementation in contemporary society. As a moderate Muslim thinker, Nurcholish Madjid emphasizes pluralism, tolerance, and the importance of broader interreligious understanding. The research focuses on two questions: (1) What are Nurcholish Madjid’s views on interfaith marriage? and (2) How is his concept implemented in present-day society? This research uses a qualitative normative juridical method with library research as the primary approach. Primary sources include the Qur’an, Hadith, and Nurcholish Madjid’s works such as Fiqh Lintas Agama and Islam Kerakyatan dan Keindonesiaan. The findings indicate that Madjid views interfaith marriage, particularly between Muslims and People of the Book (Jews and Christians), as permissible if contextualized within modern socio-historical settings. He argues that Qur’anic prohibitions are not absolute but must be understood in light of contemporary pluralism. Madjid further believes that religious diversity can strengthen social harmony through interfaith dialogue and tolerance. However, this view contrasts with Indonesia’s Islamic legal framework (KHI), which strictly prohibits interfaith marriage. The study concludes that Madjid’s thought represents a liberal-progressive approach, offering alternative perspectives on marriage law in Islam, yet remains controversial within the broader Muslim community.